Wandering spleen combined with pedicle torsion and splenic infarction: a rare case report and literature review - Cui, Qian; Xu, Xiaoyan; Li, Chang; Tang, Lihao (Frontiers in Pediatrics, 2024)
Wandering spleen (WS) concurrent with splenic pedicle torsion and infarction has been described rarely. We reported our experience in diagnosing and treating such a condition in a 16-year-old girl with acute abdominal pain. A plain CT scan showed the wandering of the spleen from the left upper quadrant. Contrast-enhanced CT indicated dilatation and distortion in the splenic vein, a counterclockwise “whirl sign” in the splenic pedicle, pancreatic tail torsion, and splenic infarction. The patient was diagnosed with WS combined with splenic pedicle torsion and splenic infarction and underwent splenectomy for treatment. She showed a satisfactory outcome during the follow-up. To enhance our understanding of it, we performed a comprehensive literature research to summarize the clinical manifestations, treatment options, and outcomes among adolescent patients.